Convergence - Poulson, Anne; Horrocks, Gary (Henry Stewart Talks, 2012)
Convergence, De-convergence, Super-convergence, Integrated student services, Library services, IT services, Estates and facilities, Learning environments, Technology enhanced learning, Subject librarianship, Research management, Teaching and learning support, Student hubs